Intramolecular Catalysis of Hydrazone Formation of Aryl-Aldehydes via ortho-Phosphate Proton Exchange - Dilek, Ozlem; Sorrentino, Anthony M.; Bane, Susan (Synlett, 2016)
Bioorthogonal site-specific chemical reaction to label biomolecules in vitro and in living cells is one of the most powerful and convenient tools in chemical biology. Reactive pairs frequently used for chemical conjugation are aldehydes/ketones with hydrazines/hydrazides/hydroxylamines. Although the reaction is generally specific for the two components, even in a cellular environment, the reaction is very slow under physiological conditions. Addition of a phosphate group at the ortho position of an aromatic aldehyde increases the reaction rate by an order of magnitude and enhances the aqueous solubility of the reagent and the product. We have synthesized phosphate-substituted aldehyde synthetic models to study kinetics of their reactions with hydrazines and hydrazides that contain a fluorophore. This rapid bioorthogonal reaction should therefore be potentially a very useful reaction for routine site-specific chemical ligations to study and image complex cellular processes in biological systems.
Keywords: site-specific conjugation; kinetics; bioorthogonal reaction